Rechnergestützte Anpassung von Laserstrahlschneidbahnen an Bauteilabweichungen - Kach, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)
Usually offline-programmed machining paths for laser cutting of complex-shaped parts have to be corrected manually in the prototype manufacture. The correction is sometimes necessary because the actual workpiece’s geometry differs from the nominal geometry used in offline-programming systems. For this reason the Dr.-Thesis develops a method for·computer-aided adaptation of machining paths for laser cutting to workpiece deviation